Application of Peptide for Improving Animal Health and Livestock Productivity - Eni Kusumaningtyas (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2018)
The use of antibiotics as growth promoter has been banned in Indonesia. One potential alternative antibiotic is peptide compounds. Peptides composed of several amino acid monomers that bind through peptide or amide bonds. Peptides are found in natural or synthetic forms that can be used to improve animal health and livestock productivity. This paper discusses the application of peptides in animal health and livestock productivity and the possibility of their utilization in Indonesia. Antimicrobial peptides are used to overcome bacterial infections, especially that are resistant to antibiotics and to preserve semen. Peptide vaccine can be used to replace conventional vaccines, especially for malignant viruses such as foot and mouth disease virus (FMD). Other peptides are used for infectious diseases and diabetes diagnostic tool in animals, medical treatment and animal reproduction system. Some peptides can be isolated from venom and have several benefits as an alternative fiber sutures for surgery and pain relief. Peptide-based drugs are metabolized faster than other small molecules, therefore, reducing the risk of contamination in livestock products.